Innovative approach to correction of organic manifestations of dysarthria in children - Sokovykh S. V. (Pedagogical innovations: from theory to practice)
In the article the author shares methodological developments in the field of speech therapy : the use of innovative speech therapy vibromassager Z-Vibe in overcoming the organic manifestations of dysarthria .
Keywords: нарушения речи; аутизм; синдром Дауна; логопедический массаж; Z-Vibe; Dysarthria; speech therapy massage; логопедический электромассажер Z-Vibe; органические проявления дизартрии; логопедический зонд